Awareness, knowledge, and practice for hepatitis B infection in Southeast Asia: a cross-sectional study - Soe, Kyi Pyar; Pan-ngum, Wirichada; Nontprasert, Apichart; Kittitrakul, Chatporn; Oam, Navuddh; Thong, Vo Duy; Tangkijvanich, Pisit; Leowattana, Wattana; Poovorawan, Kittiyod (The Journal of Infection in Developing Countries, 2019)
Introduction: The prevalence of hepatitis B virus (HBV) infection in Southeast Asia is high. Awareness and early detection are essential for timely prevention and treatment. Methodology: We examined the awareness of, knowledge about, practices and views on treatment for HBV infection in Southeast Asia. A cross-sectional survey was conducted from December 2016 to February 2017 among individuals from six nations in Southeast Asia—Myanmar, Thailand, Vietnam, Cambodia, the Philippines, and Singapore. The study population comprised healthcare and non-healthcare personnel. Results: In total, 799 healthcare personnel and 1079 non-healthcare personnel completed an online survey. The prevalence of the awareness of their own HBV infection status and risk of this regionally endemic infection was 85.6% (684/799) among healthcare personnel and 54.0% (583/1079) among non-healthcare personnel. Similarly, 85.9% of healthcare personnel and 45.5% of non-healthcare personnel had good knowledge about disease transmission, complications, and the need for treatment, and 76.6% of healthcare personnel and 39.8% of non-healthcare personnel followed good HBV infection-prevention practices. Overall, 90.6% found the idea of treatment acceptable. Awareness had a significant impact on both knowledge and practice scores among both healthcare personnel and non-healthcare personnel (p < 0.01) but without statistically significant differences in treatment acceptance between the two groups (p = 0.61). Conclusions: Awareness of HBV infection was relatively low among non-healthcare personnel in Southeast Asian populations. The provision of additional hepatitis B awareness campaigns is crucial to eliminating viral hepatitis in the region.